If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 2 + 4x Solving 4 = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 4 + -4x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 4 + -4x = 2 + 0 4 + -4x = 2 Add '-4' to each side of the equation. 4 + -4 + -4x = 2 + -4 Combine like terms: 4 + -4 = 0 0 + -4x = 2 + -4 -4x = 2 + -4 Combine like terms: 2 + -4 = -2 -4x = -2 Divide each side by '-4'. x = 0.5 Simplifying x = 0.5
| 5(1.5-w)=71.25 | | 24=4-2n | | Y=12-3y | | 4x-1=8.5 | | 14=4+5n+5n | | 5x+5=-2 | | -4x+8=-24 | | 5m+18=-5m-24-4m | | 8ln(x+2.8)=12.8 | | 2(x)-3=11 | | -8(h+59)=-96 | | 4x+6=-3 | | 3(q-5)-2=4 | | 0.33ln(5-x)=0 | | (6-y)(6-y)=0 | | 7(5x+6)=18-(1x+6) | | 4(z-18)-20=-20 | | 37.4x=54.8 | | 6x+5x=7 | | 4(0.8x+15)=2(3+1.6x) | | 7x-8-2x=12 | | 4(h+2)+3=15 | | 5wx^2-2wx^2=3 | | 5=3(p+1)-1 | | ln(x-4)xln(x^2)=42 | | 12x+5=14x-21 | | (2q)=9-3q | | (2)q=9-3q | | 2x(2x-1)=3 | | 1-6x+5x=-6 | | -540+13.50=1500 | | 16=2(s-16)+8 |